Research on LACP Multi-Active Detection and Processing Method - Peiying Wang; Zhihui Xiao; Benyuan Li (Dianxin kexue)
Virtual switching technology allows two physical devices of convergence layer to be together into a single virtual device，and the device in the access layer connects virtual device by link aggregation across devices. This simplified network is able to simplify network configuration without using MSTP and VRRP. When the member device goes wrong，the devices of the access layer is able to improve the network connection reliability relying on cross-device link aggregation. But when the link between members of the virtual device goes wrong，the virtual device will split and form two virtual devices，resulting in multi-active and causing network paralysis. Therefore，how to quickly detect multi-active and handle multi-active is extremely important for virtual switching technology development. Based on this，a fast multi-active detection method was described，which could detect multi-active quickly，and an efficient multi-active processing method was also proposed，which could effectively guarantee the normal operation of network business.